Analisis Pemberian Kompensasi Finansial dan Beban Kerja terhadap Turnover Intention pada Karyawan Bagian Operator di SPBU 34.432.17 Cipeuyeum - Aryanie Dea Jayanti; Khaerul Rizal Abdurahman (IPM2KPE, 2024)
This research aims to explore the relationship between providing financial compensation, workload, and the tendency to leave work (turnover intention) among operator employees at SPBU 34.432.17 Cipeuyeum Cianjur. This research used a qualitative approach involving 17 informants. Data was collected through interviews, observation and documentation. The triangulation process is used to ensure the validity of the data. Research findings show that according to informants' responses, providing financial compensation to operator employees is considered inappropriate and unfair. However, the workload is considered quite good. The tendency to leave work (turnover intention) is considered high. This shows that financial compensation has a significant impact on the tendency to leave work, while workload does not have a significant impact. The conclusion is that injustice and inappropriateness in providing financial compensation contribute to the high tendency to leave work. Meanwhile, workload, although considered quite good, does not have a significant impact on this trend. Therefore, companies need to pay attention to the balance between providing fair financial compensation and appropriate workloads in order to reduce the tendency of employees to leave the company. Keywords: Workload, Financial Compensation, Turnover Intention